Travel between Brussels and its outskirts: contrasting situations - Mathieu Strale (Brussels Studies, 2019)
Mobility between Brussels and its outskirts is a key multidimensional issue involving socio-economic, environmental and political challenges. However, precise data on this issue are relatively limited. In this context, this article proposes to address the issue through empirical geographical analysis. Thus, the differentiated conditions and ways of travelling to Brussels from its metropolitan area emerge, and are summarised within a typology.